2020
DOI: 10.3390/v12030322
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Queens and Virus Infections

Abstract: The honey bee queen is the central hub of a colony to produce eggs and release pheromones to maintain social cohesion. Among many environmental stresses, viruses are a major concern to compromise the queen’s health and reproductive vigor. Viruses have evolved numerous strategies to infect queens either via vertical transmission from the queens’ parents or horizontally through the worker and drones with which she is in contact during development, while mating, and in the reproductive period in the colony. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 104 publications
(196 reference statements)
2
17
0
Order By: Relevance
“…Thus far, only a limited number of studies have focused on breeding for virus resistance [27,32] despite the relevance of viruses for the health status of honey bee queens [51] and of the colony as a whole [52][53][54]. The results presented in this study confirm that breeding for virus resistance can achieve significant improvements over a limited number of generations.…”
Section: Discussionsupporting
confidence: 75%
“…Thus far, only a limited number of studies have focused on breeding for virus resistance [27,32] despite the relevance of viruses for the health status of honey bee queens [51] and of the colony as a whole [52][53][54]. The results presented in this study confirm that breeding for virus resistance can achieve significant improvements over a limited number of generations.…”
Section: Discussionsupporting
confidence: 75%
“…Potentially, our results reflect peculiarities of queen breeding operations, which are typically stationary and intensively managed with common exchanges of potentially infectious material among hives. Even though varroa is an uncommon vector of viruses to queens, our results suggest that a range of viruses can efficiently infect queens [ 16 ]. Another peculiarity of the virus survey was the lower viral prevalence in the gut than in the other two investigated tissues, contrasting with previous studies [ 19 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the biological stressors, the parasitic Varroa mite and a range of viruses have particularly profound impacts on individual and colony health [ 10 , 11 , 12 , 13 ]. Over 30 viruses have been reported from honey bees so far with pathological effects ranging from acute mortality of individuals and colony collapse to covert asymptomatic infections [ 8 , 12 , 13 , 14 , 15 , 16 , 17 ]. One of the more notorious viruses is Israeli acute paralysis virus (IAPV), which has been associated with colony collapse [ 18 ] and can affect every member of honey bee colonies with a widespread internal distribution [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Queen honey bees can acquire infectious pathogens 4043 , and are most commonly infected with sacbrood virus (SBV), black queen cell virus (BQCV), and deformed-wing virus (DWV) 33,40 . Other insects exhibit classical trade-offs between reproduction and immunity 21,25,26,4449 and we previously found that the failed queens from Survey 1 have higher copy numbers of SBV and BQCV RNA 33 .We therefore hypothesized that ovary size is linked to viral load, with the rationale that systemic viral infection is either directly impacting ovary function via pathogenic effects or depleting resources available to invest in ovariole activation via immune activation.…”
Section: Resultsmentioning
confidence: 99%